Clinical manifestations and long-term symptoms associated with SARS-CoV-2 omicron infection in children aged 0-17 years in Beijing: a single-center study - Jing Li; Jingjing Li; Ling Cao; Lin Wang; Xiaobo Chen; Wenquan Niu; Li Dang; Shuzhi Dai; Ying Wang; Menglei Ge; Weijie Liu; Qinwei Song; et al. (Frontiers Media S.A., 2024)
ObjectiveThe study aims to analyze the clinical characteristics of acute phase of SARS-CoV-2 infection in children aged 0-17 years with the Omicron variant, and summarize the persistent symptoms or new-onset clinical manifestations from 4 to 12 weeks after acute COVID. Explore the association between the vaccination status and SARS-CoV-2 neutralizing antibody levels post infection among preschool-aged children. The comprehensive study systematically describes the clinical characteristics of children infected with SARS-CoV-2, providing a foundation for diagnosis and evaluating long-term COVID in pediatric populations.MethodsThe study enrolled children who were referred to the Children's Hospital, Capital Institute of Pediatrics, (Beijing, China) from January 10, 2023 to March 31, 2023. Participants were classified as infant and toddlers, preschool, school-age, and adolescent groups. Children or their legal guardians completed survey questionnaires to provide information of previous SARS-CoV-2 infection history, as well as clinical presentation during the acute phase and long-term symptoms from 4 to 12 weeks following infection. Furthermore, serum samples were collected from children with confirmed history of SARS-CoV-2 infection for serological testing of neutralizing antibodies.ResultsThe study recruited a total of 2,001 children aged 0-17 years who had previously tested positive for SARS-CoV-2 through nucleic acid or antigen testing. Fever emerged as the predominant clinical manifestation in 1,902 (95.1%) individuals with body temperature ranging from 37.3 to 40.0°C. Respiratory symptoms were identified as secondary clinical manifestations, with cough being the most common symptom in 777 (38.8%) children, followed by sore throat (22.1%), nasal congestion (17.8%), and runnning nose (17.2%). Fatigue (21.6%), headache (19.8%) and muscle-joint pain (13.5%) were frequently reported systemic symptoms in children. The proportion of children with symptoms of SARS-CoV-2 infection varied across age groups. 1,100 (55.0%) children experienced persistent symptoms from 4 to 12 weeks post the acute phase of infection. Trouble concentrating (22.1%), cough (22.1%), and fatigue (12.1%) were frequently reported across age groups in the extended period. A limited number of children exhibited cardiovascular symptoms with chest tightness, tachycardia, and chest pain reported by 3.5%, 2.5%, and 1.8% of children, respectively. Among 472 children aged 3-5 years, 208 children had received two doses of SARS-CoV-2 vaccine at least 6 months prior to infection, and no association was found between the incidence of long-term COVID and pre-infection vaccination statuses among the 3-5 years age groups (χ2 = 1.136, P = 0.286).ConclusionsIn children aged 0-17 years infected with SARS-CoV-2 Omicron variant, fever was the primary clinical manifestation in the acute phase, followed by respiratory symptoms, systemic non-specific and digestive presentations. In particular, respiratory and digestive system symptoms were more frequent in children aged above 6 years. Regarding the long-term symptoms from 4 to 12 weeks post-infection, the most common presentations were concentrating difficulty, cough, and fatigue. The incidence of persistent symptoms of SARS-CoV-2 did not exhibit a significant correlation with vaccination status, which was attributed to the waning efficacy of the vaccine-induced humoral immune response after 6 months.